Enterococcus faecalis Sex Pheromone cCF10 Enhances Conjugative Plasmid Transfer In Vivo - Helmut Hirt (American Society for Microbiology, 2018)
ABSTRACT Cell-cell communication mediated by peptide pheromones (cCF10 [CF]) is essential for high-frequency plasmid transfer in vitro in Enterococcus faecalis. To examine the role of pheromone signaling in vivo, we established either a CF-producing (CF+) recipient or a recipient producing a biologically inactive variant of CF (CF− recipient) in a germfree mouse model 3 days before donor inoculation and determined transfer frequencies of the pheromone-inducible plasmid pCF10. Plasmid transfer was detected in the upper and middle sections of the intestinal tract 5 h after donor inoculation and was highly efficient in the absence of antibiotic selection. The transconjugant/donor ratio reached a maximum level approaching 1 on day 4 in the upper intestinal tract. Plasmid transfer was significantly lower with the CF− recipient. While rescue of the CF− mating defect by coculture with CF+ recipients is easily accomplished in vitro, no extracellular complementation occurred in vivo. This suggests that most pheromone signaling in the gut occurs between recipient and donor cells in very close proximity. Plasmid-bearing cells (donors plus transconjugants) steadily increased in the population from 0.1% after donor inoculation to about 10% at the conclusion of the experiments. This suggests a selective advantage of pCF10 carriage distinct from antibiotic resistance or bacteriocin production. Our results demonstrate that pheromone signaling is required for efficient pCF10 transfer in vivo. In the absence of CF+ recipients, a low level of transfer to CF− recipients occurred in the gut. This may result from low-level host-mediated induction of the donors in the gastrointestinal (GI) tract, similar to that previously observed in serum. IMPORTANCE Horizontal gene transfer is a major factor in the biology of Enterococcus faecalis, an important nosocomial pathogen. Previous studies showing efficient conjugative plasmid transfer in the gastrointestinal (GI) tracts of experimental animals did not examine how the enterococcal sex pheromone response impacts the efficiency of transfer. Our study demonstrates for the first time pheromone-enhanced, high-frequency plasmid transfer of E. faecalis plasmid pCF10 in a mouse model in the absence of antibiotic or bacteriocin selection. Pheromone production by recipients dramatically increased plasmid transfer in germfree mice colonized initially with recipients, followed by donors. The presence of a coresident community of common gut microbes did not significantly reduce in vivo plasmid transfer between enterococcal donors and recipients. In mice colonized with enterococcal recipients, we detected plasmid transfer in the intestinal tract within 5 h of addition of donors, before transconjugants could be cultured from feces. Surprisingly, pCF10 carriage provided a competitive fitness advantage unrelated to antibiotic resistance or bacteriocin production.